2023
DOI: 10.3389/fgene.2022.1087479
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifications in esophageal cancer: An evolving biomarker

Abstract: Esophageal cancer is a widespread cancer of the digestive system that has two main subtypes: esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EA). In the diverse range of cancer therapy schemes, the side effects of conventional treatments remain an urgent challenge to be addressed. Therefore, the pursuit of novel drugs with multiple targets, good efficacy, low side effects, and low cost has become a hot research topic in anticancer therapy. Based on this, epigenetics offers an attractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 138 publications
0
1
0
Order By: Relevance
“…Esophageal cancer (EC) globally ranks as the sixth leading cause of cancer mortality, and it significantly contributes to disease burden with its high mortality rate due to invasive manifestation and poor survival prognosis ( Lu et al, 2012 ; Tungekar et al, 2018 ; Liu WJ. et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer (EC) globally ranks as the sixth leading cause of cancer mortality, and it significantly contributes to disease burden with its high mortality rate due to invasive manifestation and poor survival prognosis ( Lu et al, 2012 ; Tungekar et al, 2018 ; Liu WJ. et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, methylation is the most studied, as it is a common modification in cell activity and can change the expression level or structural function of DNA, RNA, and proteins 20 . Many studies have found that methyltransferases can regulate tumor progression and drug resistance in the digestive system by catalyzing methylation or demethylation of cancer-related genes 21 .…”
Section: Introductionmentioning
confidence: 99%